Human Rights Education in Argentina: Notes on the process of incorporating human rights in educational contexts - Fernández, Mónica (2017)
This work provides a brief description of the various political and economic contexts that enabled the incorporation of human rights in different Argentine institutions, starting with informal education and eventually coming to form part of the curricula at all educational levels. Its purpose is to visualize how human rights education developed and which spheres of the Argentine culture drove and demanded the need for human rights and human rights education. Since one of the purposes of education is to train citizens, this article intends to show that the practice of human rights is a way of exercising citizenship and that the educational sphere is the proper context for human rights to gain respect in diverse cultural practices.